Perceptions and knowledge of sexually transmitted diseases among rural people in India: Some ground realties - Nanjunda, Dr (South East Asia Journal of Public Health, 2014)
Sexually Transmitted Diseases (STDs) have become a serious public health issue among the rural people in India because of a unique health culture and health seeking behavior. Most rural people are suffering from different types of STDs because of cultural fabrics, poverty, illiteracy, ignorance and poor access to effective treatment. The World Health Organization has also warned that India could be the next nation with the highest number of unreported STD cases, resulting in devastating consequences. This current study, conducted in a rural part of the Hassan district of Karnataka, South India, examined the perceptions and knowledge regarding STDs among rural people. A focus group study conducted among selected purposive samples of both infected (with STD) and non-infected rural people. This study has found that STDs were more prevalent among people in the age group of 25-28 years (50.6%)male respondents (62.6%), people with a low level of literacy (42.2%), professional truck drivers (38.6%), people in the lower income groups (64%), and unmarried people (56%). This study also found vaginites and herpes are the most common types of STDs found among the respondents. The majority of the respondents were not aware about the onset and symptoms of the STDs. People were too shy to seek treatment even from the local healers. Effective public health policies and health promotion programs should be developed regarding the holistic and inclusive health development for the rural people with special references to STDs. DOI: http://dx.doi.org/10.3329/seajph.v3i2.20040 South East Asian Journal of Public Health Vol.3(2) 2013: 47-51